The Origins of Terraced Temples in Egypt - Arnold, Felix (Archäologischer Anzeiger, 2024)
Some scholars have suggested that the design of Hellenistic terraced sanctuaries was based on Egyptian prototypes. On the basis of several new observations on Egyptian architecture, the paper proposes to re-frame the question in a new context. Recent studies on changes in the ancient landscape indicates, for example, that the valley temples of the Old Kingdom did not stand next to harbor basins, but on terraces within garden enclosures. They therefore could be regarded as precursors to the terraced temples of the Middle and New Kingdoms at Deir el-Bahari. This tradition appears to have been revived in the Late Period temples at Sakkara, including the temple of Imhotep/Asklepios. This building may be the ›missing link‹ between Egyptian and Hellenistic architecture: both the temple of Imhotep at Sakkara and the sanctuary of Asklepios at Kos were embellished by Ptolemy II. The paper suggests new perspectives on Egyptian-Hellenistic cultural contacts.